THE USE OF CONCEPTUAL METAPHOR IN CANCER CANCER PATIENT STORIES ON A CANCER CENTER WEBSITE - Iska Agnesya Fereralda; Shanty A.Y.P.S Duwila; Yulis Setyowati (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2022)
This research is conducted to analyse conceptual metaphor of cancer found in the stories of cancer patients. This research is aimed at explaining: (1) the source domain used to convey cancer, (2) the meaning of conceptual metaphor used by cancer patients to describe their experiences. The researcher uses a descriptive qualitative method. Therefore, this research uses content analysis as the research method. The sources of data are 5 selected stories taken from a Cancer Center Website. The results of this study show that there are three source domains of conceptual metaphors used to convey cancer. The source domains used to convey cancer are journey, blessing, and lesson. The meaning of the conceptual metaphor varies depending on the context and how it is used by the patients. As shown in the results, journey is the most frequently used source domain, with 19 metaphorical expressions, while blessing is the least frequently used source domain, with 7 metaphorical expressions. It is suggested that this research be used as a support or comparison in future research, particularly when discussing conceptual metaphors in communication. Subsequently, this research has benefited cognitive linguistics by identifying conceptual metaphors that exist in one-way communication, in this case, the cancer patients' experiences on a website.